En sus brazos se ahoga todo heroísmo. La crisis del 98 y los personajes femeninos del Quijote - Isabel Navas Ocaña (Mélanges de la Casa de Velázquez)
In the celebration of the III Centenary of Don Quixote, scheduled for the spring of 1905, there will be two current affairs on those dates: on the one hand, the crisis in which Spain has sunk after losing the last colonies in 1898, and on the other, the rise of the feminist movement, which will provoke an unusual interest in the women of Don Quixote, while reflecting on the keys to the recovery of the country. Therefore, our objective is to analyse how the female characters of Don Quixote and the figure of Cervantes were interpreted in light of these two circumstances and what role the scholars attributed to women in both the decline of Spain and its future regeneration.